Analysis of Morphometric Characteristics and Land Use in the Oued Tamri and Adoudou Watersheds, Morocco: A Spatial and Temporal Study Using GIS and Remote Sensing - Amrani, Soukaina (Journal of natural sciences, life and applied sciences, 2025)
Objectives: This research seeks to highlight the importance of using geographic information systems (GIS) and remote sensing technology to study the morphometric characteristics and patterns of human land exploitation in the Tamri and Adoudou watersheds, and to understand their role in the emergence of flash floods. Methodology: This study is based on the descriptive approach and spatial analysis using Geographic Information Systems (GIS) and remote sensing techniques to analyze the morphometric and hydrological characteristics of the Oued Tamri and Adoudou watershed. High-resolution digital data were used, such as digital elevation models (ASTER DEM) with a resolution of 12.5 meters, and satellite images (LANDSAT) obtained from reliable sources such as NASA. The data were analyzed using ArcGIS software, where morphometric and hydrological indicators (such as discharge density, concentration time, and runoff coefficient) were calculated using Spatial Analyst Results: The morphometric characteristics were estimated at 1.9 for the Tamri watershed and 2.04 for the Adoudou watershed. We adopted the theoretical difference (Ds) because it is more accurate in determining the landforms. The Ds reached 432.61 m in the Tamri and 324.7 m in the Adoudou. Thus, the theoretical difference (Ds) is limited to between 300 and 450 m, indicating that the topography of both basins is pronounced.The drainage density was 1.19 km/km² in the Tamri watershed and 1 km/km² in the Adoudou watershed, while the hydrographic density was estimated at 0.84 km-² and 0.44 km-², respectively. The water concentration time was estimated at more than 10 hours in the Tamri and more than 11 hours in the Adoudou. The speed of rainwater flow was strong, reaching 1.43 km/s in the Tamri and 1.85 km/s in the Adoudou.